PENINGKATAN KEMANDIRIAN MAHASISWA PENDIDIKAN FISIKA PADA MATA KULIAH MEKANIKA MELALUI METODE RECIPROCAL TEACHING - Fajar Fitri (Jurnal Pendidikan Fisika, 2016)
This research aims to describe thestudent independence after follow the Reciprocal Teaching of Learning. The subjects of this research are students in study program of physics education Ahmad Dahlan University who are studying Mechanics at school year of 2015/2016. Classroom Action Research consists of plan, do, and reflection. This activity repeated two cycles. The result is after follow the Reciprocal Teaching of Learning 80,3% students reached good individual and classical independence.This research aims to describe thestudent independence after follow the Reciprocal Teaching of Learning. The subjects of this research are students in study program of physics education Ahmad Dahlan University who are studying Mechanics at school year of 2015/2016. Classroom Action Research consists of plan, do, and reflection. This activity repeated two cycles. The result is after follow the Reciprocal Teaching of Learning 80,3% students reached good individual and classical independence.